Synthesis of medicinal agents from plants - Tewari, Ashish; Tiwari, Supriya (Elsevier, 2018)
Synthesis of Medicinal Agents from Plants highlights the importance of synthesizing medicinal agents from plants and outlines methods for performing it effectively. Beginning with an introduction to the significance of medicinal plants, the book goes on to provide a historical overview of drug synthesis before exploring how this can be used to successfully replicate and adapt the active agents from natural sources. Chapters then explore the medicinal properties of a number of important plants, before concluding with a discussion of the future of drugs from medicinal plants. Illustrated with real-world examples, it is a practical resource for researchers in this field. In an age of rapid environmental destruction, hundreds of medicinal plants are at risk of extinction from over collection and deforestation, limiting the amount of natural resources available for active agent extraction and threatening the discovery of future cures for diseases. Simultaneously, the demand for certain drugs occasionally outstrips the amount of an active agent that can be extracted from the source plant, threatening production. The ability to synthetically replicate the active compounds from these plants is therefore essential in creating an ecologically-aware, sustainable future for drug design.